2012
DOI: 10.1186/1471-2229-12-206
|View full text |Cite
|
Sign up to set email alerts
|

HvCKX2 gene silencing by biolistic or Agrobacterium-mediated transformation in barley leads to different phenotypes

Abstract: BackgroundCKX genes encode cytokinin dehydrogenase enzymes (CKX), which metabolize cytokinins in plants and influence developmental processes. The genes are expressed in different tissues and organs during development; however, their exact role in barley is poorly understood. It has already been proven that RNA interference (RNAi)-based silencing of HvCKX1 decreased the CKX level, especially in those organs which showed the highest expression, i.e. developing kernels and roots, leading to higher plant producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 43 publications
4
39
0
Order By: Relevance
“…This is consistent with the recent findings of Jackson et al (2013) with cultivar Q117. However, earlier results in rice (Dai et al 2001;Breitler et al 2004), barley (Travella et al 2005;Zalewski et al 2012), maize (Shou et al 2004), and fescue (Gao et al 2008) showed that AMT transformants displayed higher expression than those of BLT. The main reason for the conflicting reports appears to be the use of small amounts of minimal expression cassettes by Jackson et al (2013), which dramatically increased the frequency of simple integration events.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This is consistent with the recent findings of Jackson et al (2013) with cultivar Q117. However, earlier results in rice (Dai et al 2001;Breitler et al 2004), barley (Travella et al 2005;Zalewski et al 2012), maize (Shou et al 2004), and fescue (Gao et al 2008) showed that AMT transformants displayed higher expression than those of BLT. The main reason for the conflicting reports appears to be the use of small amounts of minimal expression cassettes by Jackson et al (2013), which dramatically increased the frequency of simple integration events.…”
Section: Discussionmentioning
confidence: 75%
“…Very few studies have directly compared integration complexity and expression levels following AMT vs. BLT in crops. Most of these studies have compared both methods side-by-side using genotypes that were amenable to both gene transfer systems but lacking commercial importance and/or based the comparison on a small number of transgenic lines (Snyder et al 1999;Dai et al 2001;Shou et al 2004;Travella et al 2005;Zalewski et al 2012;Jackson et al 2013;Joyce et al 2014). The transformation efficiency following AMT or BLT MC did not significantly differ in 12 independent experiments that generated 562 transgenic plants from the sugarcane cultivar CP88-1762.…”
Section: Discussionmentioning
confidence: 98%
“…As was already documented in the case of gene silencing [28] as well as transgene expression [29,30], this method should be the method of choice. Segregation of silencing was observed among progeny of all tested T 1 lines documenting high efficiency of the RNAi silencing process.…”
Section: Discussionmentioning
confidence: 98%
“…This method of genetic transformation is the method of choice since we documented that the biolistic approach might stimulate strong off-target effects in the case of gene silencing by siRNAs (Zalewski et al, 2012). The similar negative effect of biolistic transformation compared to the Agrobacterium -mediated method was documented in the case of transgene expression in cereals (Dai et al, 2001; Travella et al, 2006).…”
Section: Discussionmentioning
confidence: 99%